Catalyst-Free Aldol Reaction in a Water Medium - Yao, Weirong; Cui, Yanli; Wang, Peipei; Mao, Yangyi (Letters in Organic Chemistry, 2016)
Background: With growing interest in developing environmentally friendly reactions and atom-economic processes in recent years, the utilization of water as a solvent has attracted a great deal of attention. This is not only for its low-cost, safe and environmentally benign nature, but also the unique properties of water in promoting reactions. Moreover, it may afford new access to the compounds that required harsh reaction conditions under traditional approaches. The aldol reaction is one of the most useful and widely employed methods for carbon - carbon bond formation in organic synthesis. Aldols can be acted as the raw materials used for the production of lubricants, surface coatings, synthetic resins and the important intermediates in the synthesis of polyols. Methods: p-nitrobenzaldehyde (100 mg), acetone (1.5 ml) and water (2 ml) was added into a round bottom at N2 atmosphere. The suspension was stirred vigorously at 50°C for 48 h. Then the reaction mixture was diluted with brine (10ml) and extracted with 3 × 15 ml ethyl acetate. The organic layer was dried over anhydrous MgSO4. Then the ethyl acetate solution was filtered and evaporated in vacuum. The crude mixture was purified by flash column chromatography on silica gel using petroleum/ ethyl acetate (2/1) as the eluent to give the desired aldol product in 92.0%. All the compounds were spectroscopically characterized (IR, 1H NMR). Results: In the examination of electron-withdrawing groups, a pronounced steric effect was more evident in the ortho position than other positions of nitrobenzaldehydes. The electronic effect influenced the reactions dramatically. No reaction progress was detected when p-methyl benzaldehyde was employed in the identical reaction condition. With increase of carbon number of ketones the yields decreased noticeably, although the temperature was elevated to reflux situations. This was partially for the increase of substrate’s steric bulk. When the acetyl benzene was used as substrate, the reaction gave poor yield. Compared to acetone, cyclic ketones reacted more slowly in reactions. When cyclic ketones were used as substrate at 50°C, only trace amounts of the desired product were obtained. Luckily, when increasing the reaction temperature to reflux conditions, for cycloheptanone, cyclohexanone and cyclopentanone, the yields reached to 86.1%, 91.4% and 56.1% respectively. The decrease was possibly due to the influence of ring strain. More interestingly, an excellent yield was obtained when 4-methylcyclohexanone was used in the reaction. In addition, nicotinaldehyde was used to react with cyclohexanone and afforded the target product in a good yield. Conclusion: In summary, a new methodology has been developed using water as solvent and promoter that is associated with non-flammable, non-toxic reaction medium, mild conditions, easy operation and good yields. The attractive function of water in aldol reaction was observed compared with many organic solvents. The approach was expanded successively to a wide range of substrates, especially cyclic ketones.
Keywords: Aldehydes